Impact SMM And BL On Purchase Decision For Brand Love K-Pop Treasure Music Albums - Christivany, Christivany; Iskamto, Dedi (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The purpose of this study was to examine the role of brand love as a moderator between the influence of social media marketing and brand loyalty on the choice to buy K-pop treasure music albums. This research uses a quantitative approach combined with descriptive statistics. The number of research samples was 400 samples using the non-probability sample method. This research uses Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that brand love has a positive and significant effect on purchasing decisions, Brand Loyalty has a positive and significant effect on brand love, Brand loyalty has a positive and significant effect on purchasing decisions, Social media marketing has a positive and significant effect on brand love, Social media marketing has a positive and significant effect on purchasing decisions. Brand love significantly mediates the relationship between brand loyalty and purchasing decisions, and Brand love significantly mediates the relationship between social media marketing and purchasing decisions